Pengaruh Sistem Informasi Akuntansi dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Citra Abadi Sejati - Janati , Nadya Zahra; Rizqi, M. Nur; Hurriyaturrohman, Hurriyaturrohman (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze the influence of Accounting Information Systems and leadership style on employee performance at PT Citra Abadi Sejati This study is associative in nature and utilizes quantitative data obtained from questionnaires distributed to employees The research population includes all employees of PT Citra Abadi Sejati, totaling 1,561 employees. Sampling using purposive sampling method based on specific criteria resulted in a sample of 66 individuals. Hypothesis testing was conducted through partial and simultaneous tests The results indicate that the accounting information system has a positive and significant impact on employee performance, thus accepting H1 and rejecting H0. On the contrary, for leadership style variables, it is shown that leadership style does not have a positive and significant influence on employee performance, thus rejecting H2 and accepting H0 Meanwhile, simultaneously, SIA and leadership style have a positive and significant influence on employee performance, thus accepting H3 and rejecting H0.